Management of Chyloperitoneum in Laparoscopic Colorectal Surgery for Cancer: A Case Report - B. Picardi; S. Rossi; F. Cortese; S. Rossi Del Monte; G. Mazzarella; S. Molica; C. Puccioni; A. D’Urso (Case Reports in Gastrointestinal Medicine)
Chyloperitoneum after colorectal surgery remains a relatively rare complication with estimated incidence of 1%–6.5%. In colorectal surgery, this complication is mostly described after D3 right colectomy. Nonoperative treatment involves several approaches. We present a rare case of chyloperitoneum after laparoscopic left hemicolectomy for left-sided colonic adenocarcinoma. A CT scan and a triglycerides dosage on the chylous liquid were performed to confirm the diagnosis. The patient was successfully treated only by nutritional measures, avoiding prolonged fasting or invasive treatment. Fasting and complete parenteral nutrition are not necessarily required in the treatment of chyle leakage.